2016
DOI: 10.1111/echo.13351
|View full text |Cite
|
Sign up to set email alerts
|

Papillary fibroelastoma: clinical and echocardiographic features and initial approach in 54 cases

Abstract: PFE is a small tumor, predominantly valvular and benign, but entails a high incidence of cerebral embolism. The initial approach should be individualized according to clinical manifestations, comorbidities, and the experience of the surgical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The valves most frequently affected by PFEs are the mitral and aortic valves. In our experience with a total of 54 papillary fibroelastomas [5], in 29.6% (16/54) of patients, they were located in the endocardium of the left ventricle (LV), as in this case. The most common symptoms are due to a peripheral embolism, and the following symptoms have been described:…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The valves most frequently affected by PFEs are the mitral and aortic valves. In our experience with a total of 54 papillary fibroelastomas [5], in 29.6% (16/54) of patients, they were located in the endocardium of the left ventricle (LV), as in this case. The most common symptoms are due to a peripheral embolism, and the following symptoms have been described:…”
Section: Discussionmentioning
confidence: 52%
“…Several authors have reported that this type of tumor is more often seen in elderly patients with longstanding heart disease; therefore, this suggests that they occur due to mechanical damage and involve a degenerative process [6]. In accordance with this theory, in a series of 17 patients with a diagnosis of fibroelastoma, echocardiography was shown to correlate well with pathological findings, and these tumors were usually found in areas of cardiac irritation, such as the aortic and mitral valves [5]. This information proved to be very important in our case, since the damage caused by radiotherapy might have affected the valvular and subvalvular mitral apparatus, thus enhancing the potential development of this type of tumor.…”
Section: Discussionmentioning
confidence: 77%
“…Papillary fibroelastoma (PFE) accounts for 7.9%, the second most common type of benign primary cardiac tumor . PFE is usually found as solitary tumor, and multiple tumors are relatively rare with an incidence of 7%–13% of all PFE cases . The aortic valve (AV) is the most common affected site in multiple PFEs, but it remains to be clarified whether attached side of the AV may affect the incidence of embolism.…”
Section: Introductionmentioning
confidence: 63%
“…The diagnostic accuracy of echocardiography is good (80%). The diagnosable tumors include myxoma, papillary fibroelastoma, and angiosarcoma [ 18 , 19 ]. The most common tumor type is myxoma, and second is papillary fibroelastoma.…”
Section: Discussionmentioning
confidence: 99%